“Women of the waters”: workers’ perceptions of the automotive complex in Goiana/Pernambuco - Araújo, Isabelle Maria Mendes de (Argumentum, 2022)
Abstract: The arrival of multinational industrial companies into a region can trigger vulnerability dynamics, such as the introduction of the Fiat Chrysler Automobiles (FCA) automotive complex around the extractive reserve(Resex) in Goiana/Pernambuco. Resex involves four communities, composed largely of “women of the waters”, fisherwomen and female shellfish harvesters. The objective of this study is to understand the processes of vulnerability in the local context from the perception of traditional extractive workers, triggered by the arrival of the multinational FCA. We conducted field research through interview, observing Samaja’s categories for analysing social reproduction. We learned that the triplex: Capital, State and Work; is fundamental to the vulnerability to wellbeing, affecting health, nature, culture and local socioeconomic relationships.